Analisis Pergeseran Sumber Pendapatan Petani Transmigran Di Lahan Pasang Surut (STUDI KASUS DI KABUPATEN INDRAGIRI HILIR RIAU) - Teguh Hari Santosa; Sri Widodo; Masyhuri Masyhuri; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2003)
Shifting of income source transmigrant farmer in the tidal swamp from rice and palawija to non-rice happened for along time in some resettlement location in Indonesia.This ferwmenon began in 1975, in Centre Kalimantan, South Kalimantan, Jambi, South Sumatera and Riau. This problem related with constraints of low land productivity, limited labour and some problem about pests of crop. The effort of transmigrant farmer was: (1) to change some kinds of crops and cropping pattern; (2) out of tidal swamp area orientation (non farmadditional income).The objective. of this research is (1) to identify the shifting of income source of tidal swamp transmigrant farmer in Indragiri Hilir regency; (2) to analyze factors affecting the shift of the source of income in the tidal swamp.The research area is in the Indragiri Hilir regency where two districts were purposively taken and two villages from recorde data from various institution.The, Result is (1) there are shifting of income source of tidal swamp transmigrant farmer in Indragiri' Hilir, from food crop (95,63 % on 1975) to estate 'crop (53,96 % on 2002). The shifting began since 1993 and continued up to 2002; (2) Factors to influencing the source of income of estate crop is capital, farmer education, wife education, household labour, used fertilizer (TSP, KC1), lime, herbicide, pesticide and transmigrant group.Factors influencing the source of income of food crop is farmer education, household labour, used fertilizer (TSP, Ka) and pesticide.